STUDY OF THE PROFILE OF BIOLOGICALLY ACTIVE SUBSTANCES OF FRUITS OF SEA BUCKTHER OF DIFFERENT VARIETIES BY THE METHOD OF CAPILLARY ELECTROPHORESIS - O. V. Trineeva; M. A. Rudaya; A. I. Slivkin (Разработка и регистрация лекарственных средств, 2019)
Introduction. Currently, it is considered that the sea buckthorn genus includes 15 species and subspecies, but only 4 of them have found wide application in practice: the Chinese subspecies (sinensis), the European (rhamnoides), Central Asian (turkestanica) and Siberian (mongolica). Fruits of sea buckthorn have a complex chemical composition, represented by such groups of biologically active substances (BAS), as flavonoids, amino acids, organic acids, tannins, water- and fat-soluble vitamins, polysaccharides, easily digestible sugars. Most varieties of sea buckthorn bred in the Institute of horticulture Siberia M. A. Lisavenko. However, the biochemical composition of varieties adapted for growing under the conditions of the middle zone of the European part of Russia is little studied. Aim. The work was to study the BAS profile of the sea-buckthorn fruits of various varieties growing in the middle zone of the European part of Russia, by capillary electrophoresis.Materials and methods. The study of the profile of biologically active substances (free organic acids and sugars, as well as free and related amino acids) of sea buckthorn fruits of various varieties was carried out by capillary electrophoresis. The determination of the amount of free organic acids, amino acids, free and related sugars.Results and discussion. Different varieties have their phytochemical features. The sugar-acid index of the sea-buckthorn fruits of the studied varieties varied from 0.9 to 2.01, which indicates that they belong to the acidic group according to the existing gradation.Conclusion. In general, the qualitative composition of the BAS of the studied varieties is similar to each other, but it differs quantitatively. Identified varieties with a maximum and minimum content of the studied groups of biologically active substances.